Growing food on the green world: J. H. Prynne's agro-chemical pastoral in the Vale of Tintern. Issue 3 (3rd July 2018) - Eltringham, Daniel
ABSTRACT: This article reads the poetry of J. H. Prynne of the early- to mid-1970s through an ecocritical lens, arguing that this work responds to the language of a nascent environmentalism framed by the concerns of political ecology. It does so by drawing on Prynne's archival correspondence with the American poet Edward Dorn in the mid-1970s, which demonstrates a private concern with agro-chemicals, colour and cultivation that served as an analogue for shifts in the politics of relating to the extra-human world. It argues that Prynne's High Pink on Chrome (1975) is closely attuned to the suppressed human and extra-human costs of high-yield monocrop cultivation. In turn, the article sets these post-war practices in a longer continuum of pastoral suppression, linking such hidden violence with ecocritical and New Historicist arguments about the 'green' politics of William Wordsworth's 'Tintern Abbey', to which Prynne alluded when writing to Dorn in 1975.